All-fiber sixth-harmonic generation of deep UV - Wang, Yun; Lee, Timothy; De Lucia, Francesco; Abdul Khudus, Muhammad Imran Mustafa; Sazio, Pier J.A.; Beresna, Martynas; Brambilla, Gilberto (Optical Society of America, 2017)
We simulate and experimentally demonstrate deep ultraviolet generation from a 1550 nm laser source in a fully fiberized system by cascading second- and third-harmonic generation using a periodically poled silica fiber and an optical sub-micron diameter fiber. Harmonic generation is achieved by harnessing intermodal phase matching in optical microfibers and a permanent χ(2) induced via thermal poling. As a result, efficient nonlinear processes can be observed, despite the low third-order nonlinear susceptibility of silica glass.